Pengaruh Disiplin Kerja dan Kompensasi terhadap Kinerja Karyawan pada CV. Chandra Sukses Mandiri di Kota Tangerang Selatan - Titis Nurdinawati; Hafis Laksmana Nur Aldy; Bachtiar Arifudin Husain; Didi Sunardi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of Work Discipline on Employee Performance, to determine the influence of Compensation on Employee Performance and to determine Work Discipline and Compensation on Employee Performance at CV. Chandra Succeeds Independently in South Tangerang City. Research methodology with quantitative methods. The sample used in this research was 62 respondents. The analytical methods used are simple linear regression test, multiple linear regression test, coefficient of determination, correlation coefficient, partial test (t test), and simultaneous test (f test). The research results show that: 1) Work Discipline partially has a significant effect on Employee Performance at CV. Chandra Sukses Mandiri is proven by simple linear regression Y = 30.736 + 0.44X1, the coefficient of determination is 20,5% and the tvalue is 3,929 > ttable 2,001 with a significance of 0,000 < 0,05 . 2) Compensation partially has a significant effect on employee performance at CV. Chandra Sukses Mandiri is proven by simple linear regression Y = 39.140 + 0.401X2, the coefficient of determination is 17% and the tvalue is 3,537 > ttable 2,001 with a significant of 0,001 < 0,05. 3) Simultaneously there is a positive and significant influence between Work Discipline and Commensation on Employee Performance at CV. Chandra Sukses Mandiri, this can be proven by multiple linear regression Y=28.126+0.312X1+0.220X2, the coefficient of determination is 23.8%. And the fvalue is 9.236 > ftable 3.15 with a significance of 0.000 < 0.05.